Improving Second Semester Students Learning Outcornes in Sharia Business Course through the Implementation of Cooperative Learning Model Think Pair Share (TPS) In the Faculty of Economics Muhammadiyah University of North Sumatra - Siti Mujiatun (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
Hasil Penilaian Sejawat Sebidang Atau Peer Review Karya Ilmiah : Buku Improving Second Semester Students Learning Outcornes in Sharia Business Course through the Implementation of Cooperative Learning Model Think Pair Share (TPS) In the Faculty of Economics Muhammadiyah University of North Sumatra